Engineered AAV capsids mediate transduction of murine neurofibroma and sciatic nerve - Abou Haidar, Edwina; Prabhakar, Shilpa; Cheah, Pike See; Hanlon, Killian S.; Espinoza, Paula; Crain, Adam V.; Patel, Nikita; Radcliff, Greta W.; Cheng, Ming; Hernández, Iván Coto; Minderler, Steven; de la Cruz, Demitri; et al. (Springer Nature, 2025)
Genetic diseases such as Neurofibromatosis type 1 (NF1) and Charcot-Marie Tooth disease involve Schwann cells (SCs) associated with peripheral nerves. Gene therapy using adeno-associated virus (AAV) vector mediated gene delivery is a promising strategy to treat these diseases. However, AAV-mediated transduction of SCs in vivo after intravascular delivery is relatively inefficient, with a lack of extensive characterization of different capsids to date. Here, we performed an in vivo selection with an AAV9 capsid peptide display library in a mouse model of NF1. We chose one capsid variant, AAV-SC3, which was present in NF1 nerves for comparison to two benchmark capsids after systemic injection. AAV-SC3 significantly outperformed one of the two benchmark capsids at levels of transgene mRNA in the neurofibroma. Immunofluorescence microscopy revealed transgene expressing Sox10-positive SCs throughout the neurofibroma with AAV-SC3 injection. Next, we performed a pooled screen with four of the top capsids from our initial selection and AAV9 and identified one capsid, AAV-SC4, with enhanced biodistribution to and transduction of normal sciatic nerve in mice. This capsid displayed a peptide with a known laminin-binding motif, which may provide a conduit for future laminin-targeting strategies. Our results provide a baseline for future AAV-based gene therapies developed for NF1 or other diseases that affect SCs.